PROSES PENGOLAHAN DAN APLIKASI MINYAK SAWIT MERAH PADA INDUSTRI PANGAN - Ayustaningwarno, Fitriyono (Universitas Katolik Soegijapranata, 2012)
Indonesia is the largest producer of palm oil in the world. The high productivity of palm oilshould be followed by processing and diversification of processed palm oil products. One ofthe products are refined palm oil to eat. Palm oil can be processed into various kinds ofproductsfrom the stem, fruit, root. Thefruit is made into oil palm. Oil palmfroit is processedthrough handling the fruit bunches. boiling. threshing. pulverized. oil extraction. andclarification to become Crude Palm Oil (CPO). CPO has a variety of nutrients that arebeneficial to human health. such as a-, a-, ii-carotene, vitamin E (tocopherol. tokotrienol).Iicopene, lutein. sterols, unsaturatedfatty acid and ubiquinone. Generally CPO is processedinto cooking oil. However; cooking oil processing causes damage to the nutrition. To gainbenefit from the nutrients il needs to employ other treatment methods such as moleculardistillation and Supercritical Fluid Extraxtion (SFE). However. the process is still expensive.modified conventional cooking oil processing methods is also developed so that it can produceoil that still has a high nutrient. which is called Red Palm Oil (RPO). RPO can be used toreduce the risk of anemia in pregnant women. RPO when stored at room temperature can lastup to 8 months with a-carotene decrease from 500 to become 370. J ppm. With a high nutritionalvalue RPO can be used in a variety of products that are not exposed to excessive heat.including, saute oil, oils sachets for instant noodles. and salad dressings.